Antibacterial Effect of Local Propolis Extracts and Pastes Against Enterococcus Faecalis - Jumana A. AL-Jawadi; Ghada Y. Abdul Rahman; Makdad N.Chakmakchi (University of Mosul, College of Dentistry, 2014)
AIMS:The aim of this study was to determine the antibacterial effect of ethanolic and aqueous extracts and pastes of propolis against Enterococcus faecalis and compare it with that of calcium hydroxide (intracanal medicament) (in vivo and ex vivo). MATERIALS AND METHODS:The antibacterial effect of the 30%,40% ethanolic and aqueous extract of propolis as well as of calcium hydroxide were detected by the turbidity method. The turbidity of the bacterial cultures was measured by light absorption in spectrophotometer and the antibacterial effect of propolis pastes prepared from ethanolic extract as well as that prepared from aqueous extract was examined on teeth and compared with that of calcium hydroxide by colony counting method. The result were analyzed by ANOVA test and Post Hoc tests.